Uncoupling Protein 1 of Brown Adipocytes, the Only Uncoupler: A Historical Perspective - Ricquier, Daniel (Frontiers in Endocrinology, 2011)
Uncoupling protein 1 - UCP1, is a unique mitochondrial membranous protein devoted to adaptive thermogenesis, a specialized function operated by the highly specialized oxidative brown adipocytes. Whereas the family of mitochondrial metabolite carriers comprises ~40 members including UCP1, the UCP1 is specifically identified by its ability to translocate protons through the inner membrane of brown adipocyte mitochondria. Doing that, UCP1 uncouples respiration from ATP synthesis and therefore provokes energy dissipation of oxidative energy as heat while, in parallel it markedly stimulates respiration and activates fatty acid oxidation. UCP1 homologues were identified but they are biochemically and physiologically different from UCP1. Thirty five years after its identification, UCP1 still appears as a fascinating component, and the recent renewal of the interest in human brown adipose tissue makes UCP1 as a potential target for strategies of treatment of metabolic disorders.